Diversity of Salticidae (Arachnida: Araneae) in the historical and natural reserve 'Martín García Island', Argentina. Issue 11 (26th March 2016) - Marfil, M.F.; Scioscia, C.L.; Armendano, A.; González, A.
ABSTRACT: From Martín García Island were collected 975 jumping spiders, from five environments, using beating net and manual sampling methods. Saitis variegatus Mello-Leitão, 1941 was the most abundant (24.62%). The sandy xerophilous forest had the highest species richness (23 morphospecies) and jungle showed the greatest spider abundance ( n : 384). The sandy area was the least diverse and the last in relative abundance. Salticids represented 16% of the species recorded from Argentina, and the second largest family registered. The spider fauna found could be similar to that of the Southern Brasilian region, as occurs with scorpions. Two genera and two species are new records for Argentina. In addition, three new species of jumping spiders, as well as the discovery of the unknown male and female of two species, were registered. There was no record of cosmopolitan spiders or those with a large distribution range on the Island.